Probing How Counterion Structure and Dynamics Determine Polyelectrolyte Solutions Using EPR Spectroscopy - Hinderberger, Dariush; Spiess, Hans W.; Jeschke, Gunnar (Applied magnetic resonance, 2010)
In this review article, we describe how methods of electron paramagnetic resonance (EPR) spectroscopy were used to investigate polyion–counterion interactions in polyelectrolyte solutions. This subject is usually treated experimentally by light, X-ray, or neutron scattering techniques. It is shown that a large arsenal of EPR spectroscopic methods–from various sophisticated methods of line shape analysis of continuous-wave EPR, via electron spin echo envelope modulation, nanoscale distance measurements through double electron–electron resonance to high-field pulse EPR–can be used to characterize the intrinsically complicated structures formed in polyelectrolyte solutions. We show that even polymer physical models such as scaling relations can be tested in this way. The distinguishing feature with respect to the numerous scattering studies in this area is that EPR techniques are local methods , and by employing spin-carrying (i.e., EPR-active) probe ions, it is possible to examine polyelectrolytes from the counterions’ point of view .